2018
DOI: 10.5964/ejop.v14i2.1493
|View full text |Cite
|
Sign up to set email alerts
|

Therapists’ experiences in their work with sex offenders and people with pedophilia: A literature review

Abstract: This article presents a review of the literature that pertains to the experiences of therapists who work directly with child sex offenders and/or people with pedophilia. We draw together results from studies that attempted to identify how therapists experience such work and how they were personally impacted by it. Usually, such studies are embedded within one of the following theoretical frameworks: Secondary traumatic stress, compassion fatigue, vicarious traumatization and burnout. Most literature on the top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…Taken together, these findings suggest that therapists who work with clients convicted of sexual offenses may be at risk for experiencing negative mood, vicarious trauma, and countertransference reactions, but these negative psychological outcomes may be somewhat mitigated by coping and self-care strategies. However, in a recent review of the literature, Bach and Demuth (2018) concluded that while some therapists who work with individuals convicted of sex crimes are negatively affected by their work, sufficient numbers of therapists found satisfaction in the profession. Thus, the goal of this mixed-methods study is threefold.…”
Section: The Current Studymentioning
confidence: 99%
“…Taken together, these findings suggest that therapists who work with clients convicted of sexual offenses may be at risk for experiencing negative mood, vicarious trauma, and countertransference reactions, but these negative psychological outcomes may be somewhat mitigated by coping and self-care strategies. However, in a recent review of the literature, Bach and Demuth (2018) concluded that while some therapists who work with individuals convicted of sex crimes are negatively affected by their work, sufficient numbers of therapists found satisfaction in the profession. Thus, the goal of this mixed-methods study is threefold.…”
Section: The Current Studymentioning
confidence: 99%
“…and measures of distress and high levels of stress among exposed therapists (Carmel & Friedlander, 2009;Dreier & Wright, 2011;Hatcher & Noakes, 2010;Severson & Pettus-Davis, 2013). A significant effect on therapists was found on cognitive, emotional, behavioral, and physical levels (for reviews, see Bach & Demuth, 2018;Baum & Moyal, 2020). Rising awareness mental and behavioral implications has led to the understanding that special skills are necessary in order to work with this population (Knight & Modi, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…All of these terms with the exception of "burnout," which was primarily intended to evaluate stressful responses to the work environment, were originally developed to assess the effect of therapists' work with trauma survivors. In time, they were used to examine effects in a variety of populations (for instance, police officers, judges, lawyers, medical staff, and more) (for a review, see Bach & Demuth, 2018;Baum & Moyal, 2020). However, they can all be used to describe the effects of indirect secondary exposure to traumatic events or stressful situations among various populations (Bach & Demuth, 2018;Hurrell et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Sexual violence is a public health problem with serious and long-term effects for the offender and the victim, defined by the World Health Organization [1] as "any sexual act directed against a person without his consent and through the use of coercion". For this reason, there are numerous studies that have tried to discern which risk factors and personality traits can contribute to a person becoming a sex offender [2][3][4][5]. Some studies have focused on the cognitive distortions [6][7][8][9][10][11][12] that sex offenders have towards women, children, and the world in general.…”
Section: Introductionmentioning
confidence: 99%
“…This puts the thought in the offender's mind that his behavior can be repeated [14,15]. In addition to distorted belief systems, sex offenders share other crime-linked characteristics such as poor ability to achieve a dimension of intimacy, the feeling of a strong sense of loneliness and difficulty in social relationships, poor coping strategies, and low self-esteem [5,[16][17][18]. Another factor that sexual assailants seem to share is a lack of empathy, a complex emotion that requires articulated metacognitions in order for it to develop adequately [19][20][21].…”
Section: Introductionmentioning
confidence: 99%